Fulfillment of ISPO Standards on Good Plantation Practices for Independent Smallholder Palm Oil Around Mining Area in Bengkalis District - Halimah; Hadi, Syaiful; Bakce, Djaimi (JURNAL AGRICA, 2025)
Indonesian Sustainable Palm Oil (ISPO) is a standard of fulfilmment of a form of certification in sustainable development in oil palm. The purpose of this research is to analyse the achievement of ISPO standard fulfilment of independent smallholder oil palm plantations around the mining area of Bengkalis District with a special discussion is the principle pf good plantation practices. The method used was gap analysis. The method sampling the area is in stages. The method of drawing samples of respondents is deliberate. The results of the analysis of the fulfilment of ISPO oil palm plantations of independent smallholder around the mining area of Bengkalis district according to 5 principles, namely: the principle of compliance with laws and regulations is categorised as low. While the principle of implementing good plantation practices reaches and the principle of implementing transparency is categorised as very low. Furthermore, the principle of environmental management, natural resources, and biodiversity is categorised as moderate. The principle of sustainable business improvement is categorised as high.